Pengaruh Pelatihan, Tunjangan Kinerja Dan Etika Profesi Terhadap Kinerja Auditor Pada Inspektorat Jenderal Kementerian Pendidikan, Kebudayaan, Riset Dan Teknologi - Adlitama, Lazuardi; Musyaffi, Ayatulloh Michael; Perdana, Petrolis Nusa (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study is to test and analyze the effect of Training on Auditor Performance, test and analyze the effect of Performance Allowances on Auditor Performance, test and analyze the effect of Professional Ethics on Auditor Performance. The sampling technique that researchers use to select samples is using the Krejcie Table Technique. This study used primary data sources, namely through questionnaires collected from 152 employees who had auditor status at the Itjen Kemendikbudristek. The data analysis techniques used in this study are descriptive statistical analysis, validity and reliability tests, classical assumption tests, Multiple Linear Regression Analysis using SPSS version 29. This study obtained the following results: (a) Training significantly has a positive influence on Auditor Performance; (b) Performance Allowances significantly have a positive influence on Auditor Performance; (c) Professional Ethics has no influence on Auditor Performance.